(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Adverse drug reactions are frequent significant source of health issues. Liver toxicity is thefrequent causes of pharmacovigilance safety complaints and the removal of an approved medicationfrom the market over the past ten years. The liver is a key organ in the systemic detoxification deposition of chemicals, both endogenous foreign. The pharmaceutical industry drug regulatoryorganisations are also challenged by liver dysfunction in addition to healthcare professionals. Druginducedhepatotoxicity, commonly known as drug-induced liver injury (DILI), is a significant clinicalissue that has overtaken other causes of acute liver failure transplantation in Western nations. One ofthe main causes of both acute chronic liver damage is drug-induced hepatotoxicity. Using keywordslike ADR, Drug-Induced Hepatotoxicity, Hepatoprotectives, Liver Injury, Methionine, N-Acetyl -LCysteine,a thorough review explore was conducted for the current review study.